Quantification of chlorophyll content in leaves of avicennia germinans, laguncularia racemosa, durio zibethinus, garcinia mangostana, spinacia oleracea, piper betle, piper sarmentosum and centella asiatica - Arshad, Munawwarah; Kamaruddin, Sharir Aizat; Abd.Aziz, Khairul Naim; Khazali, Ahmad Suhail; Hashim, Mohd Akmal; Zulkffle, Muhammad Azhar; Hashim, Aimie Rifhan; Bakar, Latifah Munirah; Abdullah, Mohamad Zakkirun (Global Academic Excellence (M) Sdn Bhd, 2023)
This study aimed to determine chlorophyll concentrations in Avicennia germinans, Laguncularia racemosa, Durio zibethinus, Garcinia mangostana, Spinacia oleracea, Piper betle, Piper sarmentosum, and Centella asiatica. The analytical procedures required 250 mg of leaf sample to be macerated with 10 ml of 80% acetone using a pestle and mortar. The extract was centrifuged for 5 minutes at 5000 rpm. Then, the solution was transferred into a 25 ml volumetric flask and made up to 25 ml using 80% acetone. The steps were repeated by substituting with the rest of the leaf samples that would be tested. The colour intensity of green pigment was read at 645 and 663 nm for chlorophyll-a, chlorophyll-b, and total chlorophyll content using a spectrophotometer. The result revealed that the total chlorophyll content of all species ranged from 0.081-1.112 mg/g fresh weight. The chlorophyll-a concentration for all species ranged from 0.028-0.718 mg/g fresh weight; chlorophyll-b content ranged from 0.053-0.499 mg/g fresh weight. Piper sarmentosum was found to have the highest total chlorophyll content and chlorophyll-a, whereas Durio zibethinus had the highest content of chlorophyll-b. Chlorophyll has potential benefits, including improving health, boosting energy, and fighting illnesses. Additionally, chlorophyll has possible health benefits, including increased energy and the ability to fight infections.